2015
DOI: 10.1021/acs.langmuir.5b02177
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Layer Properties of a Polyaromatic Compound and its Role in Stabilizing Water-in-Oil Emulsions

Abstract: Physical properties of interfacial layers formed at the water-xylene interface by the adsorption of a polyaromatic organic compound, N-(1-hexylheptyl)-N'-(5-carbonylicpentyl) perylene-3,4,9,10-tetracarboxylic bisimide (in brief C5Pe), were studied systematically. The deprotonation of the carboxylic group of C5Pe at alkaline pH made it highly interfacially active, significantly reducing the water-xylene interfacial tension. Thin liquid film experiments showed a continuous build-up of heterogeneous C5Pe interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…That is, the acidic group immersed into the aqueous phase and the polyaromatic cores "stacked" orthogonally to the surface. And fourth, as recently shown by Bi et al 52 C5Pe is prone to the formation of heterogeneous interfacial films at the xylenewater interface which leads to stable W/O emulsions. Furthermore, BAM and atomic force microscopy (AFM) images showed that rearrangements and accumulation at the interface lead to the progressive build-up of the layer, generating a mechanically strong film.…”
Section: Introductionmentioning
confidence: 74%
“…That is, the acidic group immersed into the aqueous phase and the polyaromatic cores "stacked" orthogonally to the surface. And fourth, as recently shown by Bi et al 52 C5Pe is prone to the formation of heterogeneous interfacial films at the xylenewater interface which leads to stable W/O emulsions. Furthermore, BAM and atomic force microscopy (AFM) images showed that rearrangements and accumulation at the interface lead to the progressive build-up of the layer, generating a mechanically strong film.…”
Section: Introductionmentioning
confidence: 74%
“…where g 0 denotes the interfacial tension of the pristine water/ xylenei nterface (0.04 Nm À1 ) [57] and q is the equilibrium contact angle of the oil/water interface in the presence of SEKL/N-SEKL. Measuring q can help predict the emulsion stability, [12] because the energy of adsorption at the interface based on Equation(1) would be relativelys mall < 10 k B T if the particle is too hydrophilic (q 208)o rt oo hydrophobic (q !…”
Section: Rheological Characteristicsmentioning
confidence: 99%
“…n = 0.5, = 0 -115 o 9 n ~ 0.5 then 0.06 < n < 0.1, = 0 - Of particular interest in the current study is the contribution from surface elasticity which can be influenced by surface active species partitioning at the liquid-liquid interface. [31][32][33][34] To the authors' knowledge, interfacial effects on the spreading dynamics of droplets are rarely explored except for surfactant systems, with particular focus given to changes in surface tension. Generally, surfactants reduce the equilibrium three-phase contact angle and increase the solid-liquid contact area.…”
Section: Surface Wettabilitymentioning
confidence: 99%